Toward sustainable environmental quality: Identifying priority research questions for Latin America - Furley, Tatiana Heid (2018)
The Global Horizon Scanning Project (GHSP) is an innovative initiative that aims to identify important global environmental quality research needs. Here we report 20 key research questionsfrom LatinAmerica (LA).Members of the Society of Environmental Toxicology and Chemistry (SETAC) LA and other scientistsfrom LA were asked to submit research questions that would represent priority needs to address in the region. One hundred questions were received, then partitioned among categories, examined, and some rearranged during a workshop in Buenos Aires,Argentina. Twenty priority research questions were subsequently identified. These research questions included developing, improving, and harmonizing across LA countries methods for 1) identifying contaminants and degradation products in complex matrices (including biota); 2) advancing prediction of contaminant risks and effects in ecosystems, addressing lab-to-field extrapolation challenges, and understanding complexities of multiple stressors (including chemicals and climate change); and 3) improving management and regulatory tools toward achieving sustainable development. Whereas environmental contaminants frequently identified in these key questions were pesticides, pharmaceuticals, endocrine disruptors or modulators, plastics, and nanomaterials, commonly identified environmental challenges were related to agriculture, urban effluents, solid wastes, pulp and paper mills, and natural extraction activities. Several interesting research topics included assessing and preventing pollution impacts on conservation protected areas, integrating environment and health assessments, and developing strategiesfor identification, substitution, and design of less hazardous chemicals (e.g., green chemistry). Finally, a recurrent research need included developing an understanding of differential sensitivity of regional species and ecosystems to environmental contaminants and other stressors. Addressing these critical questions will support development of long-term strategic research efforts to advance more sustainable environmental quality and protect public health and the environment in LA.